GB1a Ameliorates Ulcerative Colitis via Regulation of the NF-κB and Nrf2 Signaling Pathways in an Experimental Model - Yu, Yuanyuan; Zheng, Congmin; Lu, Xu; Deng, Changsheng; Xu, Qin; Guo, Wenfeng; Wu, Qingye; Wang, Qi; Liu, Changhui; Huang, Xinan; Song, Jianping (Frontiers in Medicine, 2021)
Ulcerative colitis (UC), is an inflammatory bowel disease. African Garcinia Kola nuts intake has been reported as a therapy for diarrhea and dysentery in the African population. However, it is not known how the protective mechanism of action of Garcinia Kola nutsacts to ameliorates UC. Our study explored the therapeutic effects and underlying mechanism of GB1a, the main component of Garcinia Kola nuts, on dextran sodium sulfate (DSS)-induced UC. Human Colonic Epithelial Cells (HCoEpic) challenged with TNF-α were used to test the effects of GB1a in protecting against oxidative stress and inflammation in vitro. Here, We showed that GB1a could significantly attenuated DSS-induced colonic inflammatory injury, as revealed by reversed the body weight loss and disease activity index (DAI) scores of UC mice, improved the permeability of the intestinal epithelium by modulating the expression of tight junction proteins (ZO-1, Occludin). Mechanistically, GB1a could activate Nrf2 antioxidantive signaling and suppress NF-κB the nuclear translocation, consequently, resulting in reduced oxidative stress and expression of inflammatory genes induced TNF-α in HCoEpic cells. Our study suggests that GB1a alleviates inflammation, oxidative stress damage and the permeability of the colonic epithelial mucosa in UC mice via repressing the NF-κB and activating Nrf2 signaling pathway.